2020
DOI: 10.1093/mnras/staa2567
|View full text |Cite
|
Sign up to set email alerts
|

The structure of weakly magnetized γ-ray burst jets

Abstract: The interaction of gamma-ray burst (GRB) jets with the dense media into which they are launched promote the growth of local hydrodynamic instabilities along the jet boundary. In a companion paper we study the evolution of hydrodynamic (unmagnetized) jets, finding that mixing of jet-cocoon material gives rise to an interface layer, termed jet-cocoon interface (JCI), which contains a significant fraction of the system energy. We find that the angular structure of the jet + JCI, when they reach the homologous pha… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

11
47
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2
2

Relationship

1
7

Authors

Journals

citations
Cited by 70 publications
(58 citation statements)
references
References 48 publications
11
47
0
Order By: Relevance
“…Hence, the flow Lorentz factor may significantly increase compared to its value at the nozzle. Although Gottlieb et al (2020a) do not show the variation of jet Lorentz factor, this cannot be large as the jet radius prior to the reconfinement point increases only slightly in models for long GRB and only by a factor of few in their setup for short GRBs. At the nozzle, they set Γ 0 θ 0 = 0.7, which is only slightly below of Γθ 0 = 1 in our simulations.…”
Section: The Nature Of the Instabilitymentioning
confidence: 78%
See 1 more Smart Citation
“…Hence, the flow Lorentz factor may significantly increase compared to its value at the nozzle. Although Gottlieb et al (2020a) do not show the variation of jet Lorentz factor, this cannot be large as the jet radius prior to the reconfinement point increases only slightly in models for long GRB and only by a factor of few in their setup for short GRBs. At the nozzle, they set Γ 0 θ 0 = 0.7, which is only slightly below of Γθ 0 = 1 in our simulations.…”
Section: The Nature Of the Instabilitymentioning
confidence: 78%
“…When we were working on this paper, the results of a related numerical study of relativistic jets was published by Gottlieb et al (2020a). They also investigated the impact of magnetic field on the recollimation instability of relativistic jets, but in the context of gamma ray bursts (GRB), and concluded that σ 10 −2 leads to a suppression of the instability.…”
Section: The Nature Of the Instabilitymentioning
confidence: 99%
“…Such dissipation was not seen in the RMHD simulations of Bromberg & Tchekhovskoy (2016), possibly since the simulation box was too small and the jets were not sufficiently evolved. If magnetic dissipation is sufficient to reduce the magnetization to a level of σ 10 −2 , the jet continues to evolve as a hydrodynamic jet (Levinson & Begelman 2013;Gottlieb et al 2020). In this regime hydrodynamic instabilities growing on the jet boundary will cause strong mixing between jet and cocoon material and may disrupt the jet (Gottlieb et al 2021a).…”
Section: Magnetic Dissipationmentioning
confidence: 99%
“…In this regime hydrodynamic instabilities growing on the jet boundary will cause strong mixing between jet and cocoon material and may disrupt the jet (Gottlieb et al 2021a). In the intermediate regime of 10 −2 σ 1 jets are stable to both current-driven and boundary instabilities (Gottlieb et al 2020). It is therefore important to carefully analyze the jet magnetization above the nozzle and distinguish between the various cases.…”
Section: Magnetic Dissipationmentioning
confidence: 99%
“…The jet propagation in a massive star with different settings is important for understanding the dynamical properties of the GRB jet and has been investigated by phenomenological simulation studies in 2D (Aloy et al 2000;Lazzati & Begelman 2005;Morsony et al 2007;Nagakura et al 2011;De Colle et al 2012a,b;Mizuta & Ioka 2013;Duffell & MacFadyen 2015;Hamidani et al 2017;De Colle et al 2018b) and 3D (Wang et al 2008;López-Cámara et al 2013), and in the presence of magnetic fields (e.g., Tchekhovskoy et al 2010;Bromberg & Tchekhovskoy 2016;Gottlieb et al 2020Gottlieb et al , 2021. These numerical studies usually assume a long-lasting engine required for explaining the ultra-relativistic jet and its prompt gamma-ray emission.…”
Section: Introductionmentioning
confidence: 99%